Waste Marine Barnacles as Solid Catalyst for Methyl Ester Preparation Using Catfish (Pangasius) Fat as Feedstock - Intan Shafinaz, Abd Manaf; Gaanty Pragas, Maniam (2014)
The growing awareness concerning the environmental issues of energy supply and usage have recently been the topic of interest in research. Among the various alternative energy discovered, biodiesel is one of the promising blended fuel to substitute petroleum derived diesel which offers friendly and sustainable environment. Boey et al, 2011; Boey et al, 2009; nakatani et al, 2009 and Obadiah et al, 2012 revealed that many type of heterogeneous catalyst from waste, such as waste egg, crab and oyster shells; bone and ash. Barnacle is successful creatures with abundant and diverse populations. Scientists have identified about 1445 living species of which 900 are barnacle. Their abundance can create serious and expensive fouling problems on ship bottoms, buoys and pilings. Astachov et al, 2011 state that, in less than two years, 10 tons of barnacle can become attached to a tanker. In the present work, the transesterification catfish fat using barnacles as a catalyst was attempted.